Concise Review: Functional Roles and Therapeutic Potentials of Long Non-coding RNAs in Cholangiopathies - Sato, Keisaku; Glaser, Shannon; Francis, Heather; Alpini, Gianfranco (Frontiers in Medicine, 2020)
Long non-coding RNAs (lncRNAs) are RNAs with lengths exceeding 200 nucleotides that are not translated into proteins. It is well-known that small non-coding RNAs, such as microRNAs (miRNAs), regulate gene expression and play an important role in cholangiopathies. Recent studies have demonstrated that lncRNAs may also play a key role in the pathophysiology of cholangiopathies. Patients with cholangiopathies often develop cholangiocarcinoma (CCA), which is cholangiocyte-derived cancer, in the later stage. Cholangiocytes are a primary target of therapies for cholangiopathies and CCA development. Previous studies have demonstrated that expression levels of lncRNAs are altered in the liver of cholangiopathies or CCA tissues. Some lncRNAs regulate gene expression by inhibiting functions of miRNAs leading to diseased liver conditions or CCA progression, suggesting that lncRNAs could be a novel therapeutic target for those disorders. This review summarizes current understandings of functional roles of lncRNAs in cholangiopathies and seek their potentials for novel therapies.